A Collaborative Government-University-Industry Model for a STEM Career-Education Pathway: Phase III: The R&D of Forensic Analytics and Biometrics - Brown, Kathleen Elizabeth; Cheng, Dr. Joselina (Journal of Student Research, 2018)
This proposal addresses the implementation and testing of new components of forensic analytics and biometrics and how this research might be integrated into the CSI Summer Academy program that takes place each summer at the University of Central Oklahoma. The experiment designed for this proposal uses two groups of students from the university performing similar activities on computers monitored by a keystroke logger and mouse tracker to collect data. In the experiment, one group of participants is the valid user group and the other group is the hacker group. This proposal seeks to answer two main research questions using data from this experiment: What is the accuracy rate of the keystroke biometrics for detecting unauthorized users? and What is the accuracy rate of the mouse biometrics for detecting unauthorized users? The design of this proposed study is quasi-experiment, the method is quantitative, and the time scope is cross-sectional. The data from the proposed experiment will be analyzed using the multivariate analysis of variance (MANOVA) to determine whether there is any statistical evidence either supporting or rejecting the research hypothesis that behavioral biometrics can accurately identify intruders. Researchers hypothesize that there are significant differences in the ways that authentic users and hackers use the mouse and keyboard. Insights on how to stop hackers can be helpful for preventing cybercrimes. As forensic analytics and biometrics are integrated into the CSI Summer Academy, students will be introduced to an innovative, ever-expanding field of forensics that will provide them with increased technology skills and educators will be provided with new, updated teaching resources. The real-world implications of this work in the future include decreased cybercrime, a safer internet experience, increased crime prevention techniques, and even possibly lives being saved.